Hydrochemical characteristics, water quality and diatom assemblage in Dordi River, Nepal - Punam Phuyal; Shraddha Ranabhat; Sanjal Khatri; Nabin Lamichhane; Ramesh Raj Pant; Lal Bahadur Thapa; Ram Kailash Prasad Yadav (Watershed Ecology and the Environment)
Understanding hydrochemistry and diatom assemblage is important for assessing the health of aquatic ecosystems. This study has analyzed the water quality and diatom communities in the Dordi River, which is one of the major tributaries of the Marsyangdi River in Nepal. The primary research question being addressed in the study was what is the state of water quality parameters of Dordi River and how do they relate to the distribution and composition of diatoms. The water quality parameters of the river like temperature, pH, electric conductivity (EC), total dissolved solids (TDS), dissolved oxygen (DO), turbidity, and total alkalinity (TA) were measured in-situ, whereas concentrations of major ions (Ca2+, Mg2+, K+, Na+, NH4+, HCO3–, Cl–, SO42–, NO3–, and PO43–), biological oxygen demand (BOD) and chemical oxygen demand (COD) were analyzed in the laboratory by collecting water samples from different parts of the river. Piper plot, Gibbs plot, Mixing plots, redundancy analysis, and principal component analysis were applied for evaluating the spatial variation of anions and cations in water. The results showed alkaline water following the pattern: Ca2+>Mg2+>Na+>K+>NH4+ for cation and HCO3–>Cl–>SO42–>PO43–>NO3– for anion with calcium-bicarbonate dominant lithology in the river. Overall, the results highlight that the drinking and irrigation water qualities of the river were found to be excellent. Additionally, among 75 diatom species observed in the samples, the Bacillariophyceae was the dominant class covering 92% of the species. The results indicated that the diatom species richness declined as elevation increased. The distribution of diatoms was also influenced by the land use types near the water sampling points, tributaries and the main river. Overall, the physico-chemical quality of water showed significant influence on diatom species composition. The findings of this study could be useful for understanding hydrochemistry and association of water quality and diatoms in river basins of the Himalaya.